PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA BANK PERKREDITAN RAKYAT KABUPATEN GIANYAR - Hindistari, Renitha Ratu; Asri Dwija Putri, I G A M (E-Jurnal Akuntansi, 2016)
One of the cause from the phenomenon of the economic crisis that occurred in the banking sector is caused by the poor corporate governance. IICG explain good corporate governance as a structure that must be considered in running a business. This study aims to determine the effect of the application of the principles of good corporate governance on the performance of rural banks (BPR) in Gianyar. Transparency, accountability, responsibility, independence and fairness is the principle on which the implementation of GCG. Rural Bank's performance-based balanced scorecard judging from the standpoint of financial and non-financial. This study using purposive sampling method of determining the sample and data collection by using questionnaires distributed to 28 rural banks and each taken three respondents in each BPR in Gianyar. The data analysis technique used is multiple regression with level of significant 5 %. This study shows that the results of the application of the principles of good corporate governance which include transparency, accountability, responsibility, independence and fairness positive effect on the performance of Rural Banks Gianyar regency.
Keywords: good corporate governance, principles of GCG, performance